FANATISME PENGGEMAR TERHADAP ATTACK OF TITAN: (Studi Kasus Kualitatif Fenomenologi dalam Komunitas Anime Lovers Indonesia) - Meilani, Yulinda Rahma (Commsphere: Jurnal Ilmu Komunikasi, 2024)
The Attack on Titan anime has become an extraordinary phenomenon among anime lovers in Indonesia. This series attracts attention and has many fans, especially in anime-loving communities, with its tense storyline and stunning visuals. In this article, the author analyzes fan fanaticism towards Anime Attack on Titan through a qualitative phenomenological study in the Indonesian Anime Lovers community. Researchers plunged directly into the Indonesian Anime Lovers community to answer and feel what a fan's experience is, to see what forms of fanaticism exist within the community. In this article, various forms of fanaticism from Attack on Titan anime fans are found, such as changes in behavior, terror, intimidation, harassment by fans in the Indonesian Anime Lovers Community. Keywords: Fanaticism, Attack of Titan, Fans, Phenomenological.